EKSTRAKSI MINYAK DARI BIJI KURMA (Phoenix dactylifera L.) DENGAN METODE SOXHLET EXTRACTION DENGAN MENGGUNAKAN ETIL ASETAT - Taslim, Muhammad Rizky Agung, Sigit Purwanto (Universitas Sumatera Utara, 2016)
Date palm seed is one of the waste by-products generated from industrial commodities. Date seed oil can be obtained through solvent extraction using a Soxhlet apparatus. In this experiment, date palm seed was used as raw material with ethyl acetate as the solvent. The experiment was carried out by varying extraction time and the mass ratio of date palm seed to solvent. The highest oil concentration of 9.5% was obtained at date palm seed to solvent mass ratio of 1:6 with extraction time of 2 hours. Peroxide value, iodine value, specific gravity, and free fatty acid content of date seed oil were, consecutively, 0.81 meq/kg oil, 10.15 mg/g, 0.80, and 0.52%. The highest fatty acid composition of date seed oil was oleic acid at 37.22% followed by lauric acid at 19.36%.